British Missions around the Gulf, 1575-2005 : Iran, Iraq, Kuwait, Oman. - Arbuthnott, Hugh (BRILL, 2008)
Recent events have once again focused international attention on the volatile politics of the Gulf region. This new book, by three former British ambassadors demonstrates the importance of the Gulf for Britain from the days of Elizabeth I to the present. It tells the story in the four key regional states of Iran, Iraq, Kuwait and Oman.